Flat-detector computed tomography evaluation in an experimental animal aneurysm model after endovascular treatment: A pilot study. Issue 4 (August 2015) - Ott, Sabine; Gölitz, Philipp; Adamek, Edyta; Royalty, Kevin; Doerfler, Arnd; Struffert, Tobias
We compared flat-detector computed tomography angiography (FD-CTA) to multislice computed tomography (MS-CTA) and digital subtracted angiography (DSA) for the visualization of experimental aneurysms treated with stents, coils or a combination of both. In 20 rabbits, aneurysms were created using the rabbit elastase aneurysm model. Seven aneurysms were treated with coils, seven with coils and stents, and six with self-expandable stents alone. Imaging was performed by DSA, MS-CTA and FD-CTA immediately after treatment. Multiplanar reconstruction (MPR) was performed and two experienced reviewers compared aneurysm/coil package size, aneurysm occlusion, stent diameters and artifacts for each modality. In aneurysms treated with stents alone, the visualization of the aneurysms was identical in all three imaging modalities. Residual aneurysm perfusion was present in two cases and visible in DSA and FD-CTA but not in MS-CTA. The diameter of coil-packages was overestimated in MS-CT by 56% and only by 16% in FD-CTA compared to DSA ( p < 0.05). The diameter of stents was identical for DSA and FD-CTA and was significantly overestimated in MS-CTA ( p < 0.05). Beam/metal hardening artifacts impaired image quality more severely in MS-CTA compared to FD-CTA. MS-CTA is impaired by blooming and beam/metal hardening artifacts in the visualization of implanted devices. There was no significant difference between measurements made with noninvasive FD-CTA compared to gold standard of DSA after stenting and after coiling/stent-assisted coiling of aneurysms. FD-CTA may be considered as a non-invasive alternative to the gold standard 2D DSA in selected patients that require follow up imaging after stenting.